Sporadic and Periodic Interictal Discharges in Critically Ill Children: Seizure Associations and Time to Seizure Identification. Issue 2 (17th February 2023) - Sansevere, Arnold J.; DiBacco, Melissa L.; Zhang, Bo; Akhondi-Asl, Alireza; Libenson, Mark H.; Tasker, Robert C.; Pearl, Phillip L.
Abstract : Purpose: We evaluated interictal discharges (IEDs) as a biomarker for the time to development of electrographic seizures (ES). Methods: Prospective observational study of 254 critically ill children who underwent continuous electroencephalography (cEEG) monitoring. We excluded neonates and patients with known epilepsy or the sole cEEG indication to characterize events. Interictal discharges included sporadic epileptiform discharges and periodic and rhythmic patterns. Sporadic epileptiform discharges were categorized as low frequency (rare [<1/hour] and occasional [≥1/hour but <1/minute]) and high frequency (frequent, [≥1/minute] and abundant [≥1/10 seconds]). Time variables included time from cEEG start to first IED and time between first IED and ES. Results: Interictal discharges were present in 33% (83/254) of patients. We identified ES in 20% (50/254), and 86% (43/50) had IEDs. High-frequency sporadic epileptiform discharges (odds ratio [OR], 35; 95% confidence interval [CI], 14.5–88; P < 0.0001) and lateralized periodic discharges (OR, 27; 95% CI, 7.3–100; P < 0.0001) were associated with ES. Mildly abnormal EEG background without IEDs or background asymmetry was associated with the absence of seizures (OR, 0.1; 95% CI, 0.04–0.3; P < 0.0001). Time from cEEG start to first IED was 36 minutes (interquartile range, 3–131 minutes), and time between first IED and ES was 9.6 minutes (interquartile range, 0.6–165 minutes). Conclusions: Interictal discharges are associated with ES and are identified in the first 3 hours of cEEG. High-frequency sporadic epileptiform discharges and periodic patterns have the highest risk of ES. Our findings define a window of high seizure risk after the identification of IEDs in which to allocate resources to improve seizure identification and subsequent treatment.